Troubling "Environments". (27th November 2013) - Whitmarsh, Ian
<x xml:space="preserve">Abstract</x> Postgenomics is intended to move beyond the search for genes to explore disease as a result of genes interacting with their environment, revealing how they have relevance for health. This addition of environment confers genomic research with new cultural life, making it relevant to public health discourse, government interventions, and health disparities. Drawing on ethnographic research following an American genetics of asthma study conducted in Barbados, I explore the ways environment gets construed by the multiple communities involved—U.S. researchers, Bajan officials, medical practitioners, and patient participants. I draw on Lévi‐Strauss to argue that plural competing environments give mana to the American postgenomic project as intervention on racial injustice, household practices, pollution, and other aspects of asthma.